INVESTIGATING THE ROLE OF YOUGLISH WEBSITE IN TEACHING AND LEARNING PRONUNCIATION: A QUALITATIVE PERSPECTIVE - Yulistiana Yulistiana; Laila Wati; Hajriana Arfah; Usuluddin Usuluddin (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study investigated the role of the YouGlish website in teaching and learning English pronunciation. Using a qualitative descriptive design, the study was conducted with twelfth-grade students of SMAN 1 Sakra (class XII I). The data were collected through observation, questionnaires, and interview, and were analyzed thematically. The findings show that YouGlish encourages students to actively listen, repeat, and imitate native-like pronunciation, which increases their confidence and motivation. However, despite these benefits, the students also faced difficulties with suprasegmental features, accent variations, and technical issues. To overcome these challenges, they used strategies such as replaying videos, taking notes, and practicing with peers. This study concludes that YouGlish is a useful supplementary tool for pronunciation learning, especially when supported by teacher guidance and consistent practice.